Legal and ethical issues in nursing - Guido, Ginny Wacker (New Jersey : Prentice Hall, 2000)
This third edition reflects the continuing influence that the law, legal issues, and the field of ethics have on the professional practice of nursing . Professional accountability and responsibility are ever increasing, particularly as nurses become more autonomous.
Part 1. Introduction to the Law and the Judicial Process -- Part 2. Introduction to Ethics -- Part 3. Liability Issues -- Part 4. Impact of the Law on the Professional Practice of Nursing .
Includes index.
Keywords: ETHICS -- NURSING; NURSING LAW AND LEGISLATION